Pengaruh store atmosphere dan keragaman produk terhadap minat beli konsumen di Miniso Jambi Town Square - Inastria Zhafira; Dahmiri Dahmiri; Husni Hasbullah (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
In this study, the variable store atmosphere and product diversity were the research variables in Miniso Jambi town square. Because according to the author, Miniso is able to have a strong appeal in the eyes of visitors or consumers. Therefore, this study aims to determine the effect of store atmosphere and product diversity on consumer buying interest in Miniso Jambi Town Square, either partially or simultaneously. The research method used by the author is non probability sampling by distributing questionnaires to 100 respondents at the Miniso Store Jambi Town square. The data that has been collected is then processed and analyzed using the SPSS v.22 program data statistical test data. Based on the data processed and analyzed, Store Atmosphere has a positive effect on consumer Purchase Interest where the regression coefficient is 0.103 and the regression coefficient value of Product Diversity is 0.085, meaning the sig value. obtained 0.000 <0.05. It is known that the Adjusted R2 in this study is 0.341. This shows the amount of store atmosphere and product diversity on consumer purchase interest by 34.1%, while the remaining 63.9% is influenced by other unknown variables in this study.Keywords: Dividend policy, earnings volatility, leverage, stock price volatility.